2017
DOI: 10.3389/fnmol.2017.00271
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Enhances Microglial Response to OGD by Regulating p53 and PI3K/Akt Pathways with Involvement of ROS/HMGB1

Abstract: Cerebral ischemia-reperfusion injury (IRI) has a complex pathogenesis, and interleukin-17 (IL-17) is a newly identified class of the cytokine family that plays an important role in ischemic inflammation. An oxygen-glucose deprivation (OGD) model showed that IL-17A expression was significantly up-regulated in microglial cells. After IL-17A siRNA transfection, the inhibition of proliferation, and the increased apoptosis in microglial cells, induced by OGD/reperfusion, was improved, and the elevation of Caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…When HMGB1 binds to the upregulated RAGE, some protein kinases in mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3 kinase/protein kinase B (PI3K/Akt) pathways, such as p38 kinase, SAPK/JNK, extracellular regulated protein kinases1/2 (ERK 1/2) and Akt are activated by this mitogen (Qin et al, 2009; Tong et al, 2018); in addition, cell division cycle 42 (Cdc42), Ras-related C3 botulinum toxin substrate (Rac), and just another kinase/signal transducer and activator of transcription 1 (JAK/STAT1)-mediated signal transduction pathways are also activated (Tsoyi et al, 2010). These events finally lead to the translocation of NF-κB, inducing the expression of inflammatory cytokines and chemokines that participate in the maturation and migration of immune cells, the expression of surface receptors and growth of neurites, as well as tumor proliferation (Muhammad et al, 2008; Akirav et al, 2012; Zhang et al, 2017).…”
Section: Receptors and Transduction Pathways Of Hmgb1mentioning
confidence: 99%
“…When HMGB1 binds to the upregulated RAGE, some protein kinases in mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3 kinase/protein kinase B (PI3K/Akt) pathways, such as p38 kinase, SAPK/JNK, extracellular regulated protein kinases1/2 (ERK 1/2) and Akt are activated by this mitogen (Qin et al, 2009; Tong et al, 2018); in addition, cell division cycle 42 (Cdc42), Ras-related C3 botulinum toxin substrate (Rac), and just another kinase/signal transducer and activator of transcription 1 (JAK/STAT1)-mediated signal transduction pathways are also activated (Tsoyi et al, 2010). These events finally lead to the translocation of NF-κB, inducing the expression of inflammatory cytokines and chemokines that participate in the maturation and migration of immune cells, the expression of surface receptors and growth of neurites, as well as tumor proliferation (Muhammad et al, 2008; Akirav et al, 2012; Zhang et al, 2017).…”
Section: Receptors and Transduction Pathways Of Hmgb1mentioning
confidence: 99%
“…Previous studies have shown that hypoxia-induced ROS could enhance HMGB1 secreted into extracellular in the normal human nasal epithelium cells ( Min et al, 2017 ); ROS could also regulate HMGB1/IL-17A axis to promote the apoptosis in microglial cells ( Zhang et al, 2017 ). Excessive production of ROS itself can cause cell damage; HMGB1 can act as a molecular danger to sense cell damage; therefore, some close connections may exist between them.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that these two stimulants can stimulate cells from both ends of the signaling pathway (Figure ) to induce changes in the nodes of the pathway. Based on these results and previous reports, the investigators speculated that the overexpression of HBx could inhibit the activity of NF‐κB in normal hepatocytes, and NF‐κB, HMGB1 and ROS were mutually regulated, TLR4 is also involved in regulation. Therefore, the investigators conclude that HBx suppresses the expression of HMGB1 and the production of ROS through NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%